Angst som eksistentiale i Inger Christensens det - Floris Christensen, Markus (Passage - Tidsskrift for litteratur og kritik, 2022)
This article offers a systematic reading of the representation of anxiety in Inger Christensen’s it (1969) by chronologically mapping the development of the theme across the work’s three main sections, Prologos, Logos and Epilogos. Moreover, this article posits a new approach to the material, arguing that, rather than Søren Kierkegaard’s theological-psychological framework, Martin Heidegger’s fundamental ontological concept of anxiety may positively shed light on Christensen’s thematization of anxiety in the work. It is one of the aims of the article to show that Heidegger’s concept of anxiety can advantageously expand the understanding of Christensen’s representation of anxiety, as Heidegger’s confrontation with metaphysics, his In-Frage-stellen of the forgetfulness of Being, seems particularly compatible with Christensen’s poetics of systemic modernism. I examine how anxiety manifests itself in the architecture of the work, and I argue that Heidegger’s fundamental ontological interpretation of the concept may highlight some central features of the representation of anxiety that Kierkegaard’s theory of anxiety does not seem to capture.